A holistic view of mammalian (vertebrate) cellular iron uptake. Issue 9 (7th August 2020) - Kosman, Daniel J.
Abstract : Ectodomain, reductive iron uptake mediated by a ZIP transporter and the canonical, endosomal DMT1-mediated pathway. Abstract : Cell iron uptake in mammals is commonly distinguished by whether the iron is presented to the cell as transferrin-bound or not: TBI or NTBI. This generic perspective conflates TBI with canonical transferrin receptor, endosomal iron uptake, and NTBI with uptake supported by a plasma membrane-localized divalent metal ion transporter, most often identified as DMT1. In fact, iron uptake by mammalian cells is far more nuanced than this somewhat proscribed view suggests. This view fails to accommodate the substantial role that ZIP8 and ZIP14 play in iron uptake, while adhering to the traditional premise that a relatively high endosomal [H+] is thermodynamically required for release of iron from holo -Tf. The canonical view of iron uptake also does not encompass the fact that plasma membrane electron transport – PMET – has long been linked to cell iron uptake. In fact, the known mammalian metallo-reductases – Dcytb and the STEAP proteins – are members of this cohort of cytochrome-dependent oxido-reductases that shuttle reducing equivalents across the plasma membrane. A not commonly appreciated fact is the reduction potential of ferric iron in holo -Tf is accessible to cytoplasmic reducing equivalents – reduced pyridine and flavin mono- and di-nucleotides and dihydroascorbic acid. This allows for the reductive release of Fe 2+ at the extracellular surface of the PM and subsequent transport into the cytoplasm by a neutral pH transporter – a ZIP protein. What this perspective emphasizes is that there are two TfR-dependent uptake pathways, one which does and one which does not involve clathrin-dependent, endolysosomal trafficking. This raises the question as to the selective advantage of having two Tf, TfR-dependent routes of iron accumulation. This review of canonical and non-canonical iron uptake uses cerebral iron trafficking as a point of discussion, a focus that encourages inclusion also of the importance of ferritin as a circulating 'chaperone' of ferric iron.